Mass strandings of cold-stunned loggerhead turtles in the south Iberian Peninsula: ethological implications - Bellido López, Juan Jesús; Baez, Jose Carlos; Mons Checa, Jose Luís; Martín-Jaime, Juan Jesús; Castillo, Juan José; Real-Giménez, Raimundo; Sanchez, Rafael (Taylor and Francis, 2010)
The loggerhead Caretta caretta is the most frequent marine turtle in the Mediterranean Sea and adjacent waters (Margaritoulis et al. 2003). In the Mediterranean Sea strandings of cold-stunned loggerheads have been rarely recorded (Bentivegna et al. 2002). However, similar events are frequent in others regions, e.g. the Atlantic Ocean and the Gulf of Mexico (Brongersma 1982, meylan 1986, morreale et al. 1992, Witherington & erhart 1989). A recent report of a group of cold-stunned loggerheads stranded in the Adriatic Sea was related to a temperature decrease of 6 ºC (Bentivegna et al. 2002). We report three new cases of groups of loggerheads stranded with symptoms of cold-stunning on the Andalusia coast (South of Spain), which is an outstanding area for the loggerhead in the North Atlantic-Mediterranean region, as it connects the West ern Mediterranean Sea with the Atlantic Ocean (e.g. Camiñas & De la serna 1995, Camiñas 1997). The aim of this work was to analyze the temporal variation of loggerheads strand ed with symptoms of cold-stunning along the Andalusian coastline, from 2001 to 2007. For this purpose, we tested the relationship between the stranding events and oceanographic factors. The ecological and ethological implications are discussed.
La versión posprint (aceptada) coincide con la publicada (pdf del editor)
Keywords: Tortugas marinas - Efectos del frío - Andalucía; Mass strandings; Ethological implications; Loggerhead turtles; Cold-stunned